QUANTIFICATION OF PREDATION AND INCIDENCE OF PARASITIC INFESTATION IN MELGHAT TIGER RESERVE WITH SPECIAL REFERENCE TO LEOPARDS (PANTHERA PARDUS) - M. V. SHIRBHATE (The Bioscan, 2007)
135 scats of Leopards from Melghat Tiger Reserve were analyzed for any undigested remains. The analysis of scats of leopards revealed remains of 11 prey species with a high preponderance of small mammals including Indian hare (Lepus nigricollis) , sambar (Cervus unicolor)and wild pig (Sus scrofa). The prey preference on the basis of biomass was sambar>wild pig>domestic animals> chital>four horned antelope. but the order of predation on the basis of undigested remains in scats was Indian hare > sambar > wild pig > langur > domestic animals. It is found that the leopards preferred two different preys (55 scats, 40.47%) at a time. Leopards were also found to be the host of a number of gastrointestinal parasites. They got these infections from the herbivores on which they feed as well as crabs on which they preyed rarely.